The Art of Ukiyo-e from the Perspective of Hierarchical Concepts - Chen Qiu; Issarezal Ismail; Ishak Ramli; Weiqin Pan; Hamidi Hadi (Pascasarjana ISBI Bandung Conference Series, 2025)
The aims of this study are to analyze ukiyo-e art from the perspective of hierarchical concept, and to expound the influence of hierarchical concept on the development of ukiyo-e art from three aspects: production process, style characteristics and commercial cooperation. Ukiyo-e art can be called the representative of Japanese art, and its emergence and development are caused by multiple reasons. In the process of its growth and development, there are many factors affecting and restricting it. It is suitable for qualitative research because of its flexibility in looking at ukiyo-e art from a hierarchical perspective. Overall, this study will provide an invaluable source of information about ukiyo-e art. It will benefit artists, researchers, art students, and scholars interested in studying this theme and field. Keywords: Ukiyo-e; Hierarchical Concepts; woodcut